Intervention on the Status of Unwed Children After the Constitutional Court Decision - Terbit Fajar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Intervention on the status of children out of wedlock after the decision of the constitutional court and what constitutional judges considerations in issuing Decision Number 46 / PUU-VIII / 2010. This type of research is a type of normative legal research with a statute approach and conceptual approach. Sources of legal materials used are primary, secondary and tertiary legal materials. The legal material collection technique used is the literature study technique and then arranged descriptively and systematically. The results showed that (1) Since the Constitutional Court ruling No. 46 / PUU-VIII / 2010, an extramarital child can have a civil relationship with a man as his father if it can be proven by science and technology that the child has a blood relationship with the man. (2) Children are the result of a mother and father relationship either because of sexual relations or because other actions are in accordance with technological developments that can cause pregnancy, therefore the Constitutional Court judge granted judicial revew of Article 43 paragraph (1) of the 1945 constitution.